Trends of improving governance on the basis of electronic administration technologies - L. Alekseeva (Publishing House of the State University of Management, 2016)
The author explores the process of introduction of information technologies in public administration and the emerging trends in improvement of governance through the introduction of electronic technology. The author identifies priorities electronic government solutions. The article analyzes state of the IT industry in Russia and prospects of its development. The author indicates problems introduction of electronic technologies in public administration.